IDIOPATHIC HYPERTROPHIC PACHYMENINGITIS: Idiopathic Hypertrophic Disease - Nafees, Muhammad; Akram, Muhammad Hamid (Pakistan Armed Forces Medical Journal, 2009)
INTRODUCTION Idiopathic hypertrophic pachymeningitis (IHP) is a clinical disorder characterized by localized or diffuse thickening and fibrosis of dura matter with no underlying cause demonstrable [1]. IHP is a rare disorder affecting men more than women [2] with peak incidence in 6th decade of life [3]. Common clinical features include headache, multiple cranial nerve palsies and cerebellar dysfunctions occurring alone or in combination. We present a case of a lady, who was diagnosed in our department after suffering from the disease for some time with no diagnosis available.